2014
DOI: 10.9775/kvfd.2013.10321
|View full text |Cite
|
Sign up to set email alerts
|

Leiomyomas of Oviduct and Its Ventral Ligament of Hens: Immunohistochemical Evaluation and the Plasma Concentration Levels of 17 β-Oestradiol and Progesterone

Abstract: SummaryLeiomyoma's of the oviduct and its ventral ligament (VL) are common tumours of the domestic fowl which develop after the end of the first laying season. In the present study, macroscopic, microscopic, and immunohistochemical features of the leiomyomas of the reproductive tract and their prevalence were investigated in commercial laying hens. In 60-90 weeks old commercial laying hens, toward the end of the first laying period, the incidence of genital tract leiomyomas were determined as 10.43%. Of these,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Neoplasms originating from the oviduct are less common compared to ovarian tumours (Echols & Speer, 2022 ). Adenoma, adenomatous hyperplasia (Echols & Speer, 2022 ), adenocarcinoma (Carleton & Garner, 2002 ; Schmidt et al., 2015 ), hemangiosarcoma (Rosen, 2012 ), lymphoid leukosis (Greenacre, 2015 ), carcinomatosis (Rosen, 2012 ), granulosa cell tumour (Robat et al., 2017 ), dysgerminoma (Strunk et al., 2011 ), leiomyoma (Anjum et al., 1988 ; Tunca et al., 2014 ) and rarely LMS (Antinoff et al., 1997 ) have been reported in the reproductive tract of female birds. Conventional LMS has also been reported in the skin and subcutis (Nemeth et al., 2016 ; Timurkaan et al., 2016 ), large intestine (Cardoso & Levy, 2014 ), jejunum (Steinberg, 1988 ) and anterior limb (Bonel et al., 2019 ) of pet birds.…”
Section: Discussionmentioning
confidence: 99%
“…Neoplasms originating from the oviduct are less common compared to ovarian tumours (Echols & Speer, 2022 ). Adenoma, adenomatous hyperplasia (Echols & Speer, 2022 ), adenocarcinoma (Carleton & Garner, 2002 ; Schmidt et al., 2015 ), hemangiosarcoma (Rosen, 2012 ), lymphoid leukosis (Greenacre, 2015 ), carcinomatosis (Rosen, 2012 ), granulosa cell tumour (Robat et al., 2017 ), dysgerminoma (Strunk et al., 2011 ), leiomyoma (Anjum et al., 1988 ; Tunca et al., 2014 ) and rarely LMS (Antinoff et al., 1997 ) have been reported in the reproductive tract of female birds. Conventional LMS has also been reported in the skin and subcutis (Nemeth et al., 2016 ; Timurkaan et al., 2016 ), large intestine (Cardoso & Levy, 2014 ), jejunum (Steinberg, 1988 ) and anterior limb (Bonel et al., 2019 ) of pet birds.…”
Section: Discussionmentioning
confidence: 99%
“…2,65 These tumors are usually slow growing and are often incidental findings at necropsy in commercial chickens. 85 Spontaneous leiomyomas of the oviduct and its ventral ligament are common tumors of chickens that typically develop after the end of the first laying season, 85,86 with a reported incidence of 10.4% in 60-to 90-week-old laying hens. 85 It is noteworthy that despite chickens being the most numerous species in our study population, we identified only a single case of leiomyoma in a chicken, and the tumor affected the intestines rather than the oviduct.…”
Section: Discussionmentioning
confidence: 99%
“…85 Spontaneous leiomyomas of the oviduct and its ventral ligament are common tumors of chickens that typically develop after the end of the first laying season, 85,86 with a reported incidence of 10.4% in 60- to 90-week-old laying hens. 85 It is noteworthy that despite chickens being the most numerous species in our study population, we identified only a single case of leiomyoma in a chicken, and the tumor affected the intestines rather than the oviduct. In pheasants (family Phasianidae), cecal leiomyomas have been reported to occur in conjunction with chronic Heterakis spp.…”
Section: Discussionmentioning
confidence: 99%